Presence of Borrelia burgdorferi in endomyocardial biopsies in patients with new-onset unexplained dilated cardiomyopathy - Palecek, Tomas; Kuchynka, Petr; Hulinska, Dagmar; Schramlova, Jana; Hrbackova, Hana; Vitkova, Ivana; Simek, Stanislav; Horak, Jan; Louch, William E; Linhart, Ales (Medical microbiology and immunology, 2010)
Dilated cardiomyopathy (DCM) represents the third most common cause of heart failure and the most frequent cause of heart transplantation. Infectious, mostly viral, and autoimmune mechanisms, together with genetic abnormalities, have been reported as three major causes of DCM. We hypothesized that Lyme disease (LD), caused by spirochete Borrelia burgdorferi (Bb), might be an important cause of new-onset unexplained DCM in patients living in a highly endemic area for LD such as the Czech Republic. We performed endomyocardial biopsy (EMB) in 39 consecutive patients presenting with symptomatic unexplained left ventricular (LV) systolic dysfunction lasting no more than 12 months. In eight subjects (21%), Bb was detected in the EMB sample by polymerase chain reaction or by electron microscopy. None of these patients exhibited any form of atrioventricular block or other extracardiac manifestation of Bb infection. Serological testing identified IgG antibodies against Bb in only two cases and IgM antibodies in none. All affected patients were treated with intravenous ceftriaxone for 3 weeks. At 6 months follow-up, LV morphology and function as well as functional status of these patients significantly improved. In conclusion, Bb infection may represent an important cause of new-onset unexplained DCM in patients living in endemic regions such as the Czech Republic. Because the antibiotic treatment appears to be markedly effective and serological examination does not provide a tool for diagnosing the disease, EMB focused on the detection of Bb should be performed in all patients from endemic areas with new-onset unexplained DCM not responding to conventional therapy.
Keywords: protilátky bakteriální; Microscopy, Electron; Ventricular Dysfunction, Left; dysfunkce levé srdeční komory; Prevalence; Anti-Bacterial Agents; Ceftriaxone; elektronová mikroskopie; polymerázová řetězová reakce; Česká republika; Polymerase Chain Reaction; Middle Aged; mužské pohlaví; prevalence; Biopsy; Adult; Czech Republic; lymeská nemoc; Borrelia burgdorferi; ženské pohlaví; myokard; Humans; Cardiomyopathy, Dilated; dilatační kardiomyopatie; Antibodies, Bacterial; Myocardium; antibakteriální látky; lidé středního věku; ceftriaxon; biopsie; Lyme Disease; dospělí; Female; lidé; Male